Emergency Management of Preeclampsia-Eclampsia at Primary Services in Surabaya - Endah Suprihatin; Sri Hardi Wuryaningsih (Journal of Global Pharma Technology, 2020)
To reduce maternal mortality due to the relay referral system, initial doses of Sulfas Magnesium (SM) therapy have been established in primary care before being referred, but in practice, magnesium sulfate drugs are often not available at the primary care level or are not used according to guidelines. This study aims to explore the management of emergency preeclampsia-eclampsia in primary services in Surabaya. This research was conducted in 5 primary health services in Surabaya. The sample in this study was health workers who carried out emergency management of the preeclampsia and were selected by disaproportionate stratified random sampling, which consisted of doctors, midwives, and nurses. Data were analyzed using Partial Least Square (PLS). The results showed that organizational characteristics and individual characteristics significantly affected the management of emergency preeclampsia-eclampsia. The magnitude of the coefficient estimate for the characteristics of the officers for the management of emergency preeclampsia-eclampsia was 0.277669 and for the management of emergency preeclampsia / eclampsia was 0.284305. The coefficient was positive, meaning that the better the characteristics of the organization and health workers, the higher the accuracy of the management of emergency preeclampsia. The results of the study indicated that primary health services in Surabaya need to increase the provision of facilities and infrastructure as well as drugs for emergency management of preeclampsia and eclampsia, for health workers it is advisable to increase knowledge especially about the administration of initial doses of magnesium sulfate in preeclampsia-eclampsia patients before being referred. Keywords: Preeclampsia, Eclampsia, Emergency Management, Primary Health Services